2013
DOI: 10.1002/jgra.50548
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of substorm injections with the subauroral geospace: 1. Multispacecraft observations of SAID

Abstract: [1] Subauroral ion drifts (SAID) are the prominent feature of the active subauroral geospace, just earthward of the electron plasma sheet (PS) boundary in the premidnight sector. We explore magnetically conjugate satellite observations of substorm SAID near the magnetic equator and in the topside ionosphere confirming and expanding on our previous results. The SAID channels reside between the hot electron (PS/auroral) boundary at the plasmapause and the drop in the hot ion flux inside the plasmasphere. The ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
216
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(230 citation statements)
references
References 105 publications
(153 reference statements)
14
216
0
Order By: Relevance
“…Previous works have implied that SAIDS and SAPS are generated in the same way (e.g., Mishin, 2013). However, SAIDs are more closely associated with substorms (Anderson et al, 1993).…”
Section: Model Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous works have implied that SAIDS and SAPS are generated in the same way (e.g., Mishin, 2013). However, SAIDs are more closely associated with substorms (Anderson et al, 1993).…”
Section: Model Resultsmentioning
confidence: 96%
“…However, recent works (e.g., Mishin, 2013) have reported that R2 FACs are concentrated near the poleward boundary of SAPS and do not enclose the channel, which is inconsistent with the current-generator theory. Alternatively they have proposed another concept that a SAPS is a turbulent plasmaspheric boundary layer via a short circuiting of the plasmoid within the ambient plasma in the plasmasphere (e.g., Mishin, 2013).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations